1992
DOI: 10.1080/00288330.1992.9516529
|View full text |Cite
|
Sign up to set email alerts
|

Ecological studies on two intertidal New Zealand fishes,Acanthoclinus fuscusandForsterygion nigripenne robustum

Abstract: Population density, seasonal abundance fluctuations, and habitat preferences of Acanthoclinus fuscus and Forsterygion nigripenne robustum were studied in the rocky intertidal zone at Kaikoura, New Zjaland, from August 1988 to June 1989. Monthly recaptures of marked fishes showed that A. fuscus was common on rocky platforms with small shallow pools; F. n. robustum occurred under larger stones and in deeper channels or larger pools. Most captured A. fuscus were juveniles and adolescents; no seasonal fluctuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These two possibilities about diel habitat utilisation (same/different individuals coming to occupy a tidepool) are not mutually exclusive and may be operating simultaneously in nature. Studies on homing behaviour also noted the occurrence of ''unmarked individuals'' (new comers) and some marked individuals were not recaptured at the original tidepools (Gibson 1967;Richkus 1978;Berger and Mayr 1992;Yoshiyama et al 1992;Gibson 1999). This suggests that some members of a tidepool fish assemblage are exchanged while others return to the same pools.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These two possibilities about diel habitat utilisation (same/different individuals coming to occupy a tidepool) are not mutually exclusive and may be operating simultaneously in nature. Studies on homing behaviour also noted the occurrence of ''unmarked individuals'' (new comers) and some marked individuals were not recaptured at the original tidepools (Gibson 1967;Richkus 1978;Berger and Mayr 1992;Yoshiyama et al 1992;Gibson 1999). This suggests that some members of a tidepool fish assemblage are exchanged while others return to the same pools.…”
Section: Discussionmentioning
confidence: 89%
“…Firstly, the same individuals may occupy and return to a particular tidepool in a 24-h cycle while being absent during certain hours of day. According to studies on homing behaviour, some fishes repeatedly occupy the same tidepool/set of tidepools (Richkus 1978;Berger and Mayr 1992;Yoshiyama et al 1992). If such a situation prevails in our study site, it means that fishes have different home ranges by day and at night.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, it has peculiarities on its lateral line, implying that ecologically divergent species can be caused by a process of functional adaptation with the main selective pressure being the level of background hydrodynamic activity (Feary & Clements, 2006;Berger & Mayr, 1992;Wellenreuther et al, 2010). Besides, it has peculiarities on its lateral line, implying that ecologically divergent species can be caused by a process of functional adaptation with the main selective pressure being the level of background hydrodynamic activity (Feary & Clements, 2006;Berger & Mayr, 1992;Wellenreuther et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The present study examined the reproduction of Gobius paganellus L. 1758, Gobius bucchichi Steindachner 1870, Gobius cobitis Pallas 1814, Parablennius sanguinolentus (Pallas 1814), Salaria pavo (Risso 1810), Tripterygion tartessicum Carreras‐Carbonell et al, [previously identified as Tripterygion tripteronotum and mentioned as such in Compaire et al, ] and Symphodus roissali (Risso 1810). Although intertidal fish species exhibit diverse reproductive modes (Balon, ), all the families analysed in this study are oviparous (Gobiidae: Miller, ; Blenniidae: Patzner, ; Tripterygiidae: Berger & Mayr, ; Labridae: Potts, ). Demersal spawners produce eggs that are attached to one another or to physical or biological substrata (DeMartini, ).…”
Section: Introductionmentioning
confidence: 99%